2013
DOI: 10.1590/s2176-94512013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Class II malocclusion treatment using high-pull headgear with a splint: a systematic review

Abstract: While there is still a lack of strong evidence demonstrating the effects of high-pull headgear with a splint, other studies indicate that the anteroposterior relations improve due to distalization of the maxilla and upper molars, with little or no treatment effects in the mandible. Greater attention to the design should be given to improve the quality of such trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
2
13
0
1
Order By: Relevance
“…The 14 SRs included and the data extracted from each SR are shown in Table . One‐third of the included SRs (5 of 14) were integrated with MA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 14 SRs included and the data extracted from each SR are shown in Table . One‐third of the included SRs (5 of 14) were integrated with MA .…”
Section: Resultsmentioning
confidence: 99%
“…The 14 SRs included and the data extracted from each SR are shown in Table 4 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). One-third of the included SRs (5 of 14) were integrated with MA (18,20,28,30,31).…”
Section: Papers Selectionmentioning
confidence: 99%
“…[1][2][3][4] However, despite the potential for achieving desirable treatment results, the success of this treatment modality depends heavily on patient cooperation. 5,6 It has previously been shown that compliance with headgear use has a significant effect on treatment outcome and duration. [6][7][8] In the orthodontic specialty, there was a rapid increase in the use of headgear through the mid1980s followed by a decline in the routine use of this appliance from 1996 to present.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 It has previously been shown that compliance with headgear use has a significant effect on treatment outcome and duration. [6][7][8] In the orthodontic specialty, there was a rapid increase in the use of headgear through the mid1980s followed by a decline in the routine use of this appliance from 1996 to present. [9][10][11] Interestingly, over the years the headgear treatment modality has been in and out of favor.…”
Section: Introductionmentioning
confidence: 99%
“…They were similar to reductions described for cervical-pull (À0.6 to À0.88/y) and high-pull (À0.5 to À1.18/y) headgear. 32,33 This was a dentoalveolar treatment effect. Since the Herbst appliance is attached with rigid steel arms to the first molars, the same force that displaces the mandible down and forward is reciprocally exerted on the maxilla.…”
Section: Discussionmentioning
confidence: 97%